Implementation of Knowledge Management in Different Industries - Mukhtar Hanafi; Andi Widiyanto; Nuryanto Nuryanto; Hafidz Fahrizal Rahman; Mohammad Rahardian Adhitama (International Journal of Informatics and Information Systems, 2021)
Customer knowledge is a valuable asset, and gathering, managing, and sharing customer knowledge can be a useful competitive activity for organizations. Successful knowledge partnerships with essential and valuable customers can strengthen business performance and create an absolute competitive advantage that is difficult for competitors to emulate. In consumer knowledge management, companies often experience significant obstacles or constraints so that sometimes many companies prevent them from managing consumer knowledge. The company or organization depends on consumers who do not need to understand the industrial field of the company or organization. This paper discusses the comparison of the application of customer knowledge management in various industries. Research findings that all organizations must apply the three essential components of customer-related knowledge within the underlying conceptual framework. Three basic components of customer-related knowledge within a basic conceptual framework: knowledge for customers, knowledge of customers, and customer knowledge, cannot be eliminated. This proves the compatibility with previous studies. In fact, to succeed, they must be applied so that it is of value to the company. Implementation of the framework can present a great opportunity for the organization or company to make new products so that this will improve the performance of the company or organization and maintain the continuity of the company or organization.